2022
DOI: 10.1007/s00415-022-11500-5
|View full text |Cite
|
Sign up to set email alerts
|

Proximal hyperdense middle cerebral artery sign is associated with increased risk of asymptomatic hemorrhagic transformation after endovascular thrombectomy: a multicenter retrospective study

Abstract: Objective To investigate whether hyperdense middle cerebral artery sign (HMCAS) on pretreatment no-contrast CT (NCCT) is associated with hemorrhagic transformation (HT) after endovascular thrombectomy (EVT). Methods Patients with acute middle cerebral artery (MCA) occlusion who received EVT in three comprehensive hospitals were retrospectively evaluated. They were divided into four groups based on the presence or absence of HMCAS and corresponding CTA find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The presence of proximal HMCAS was strongly associated with higher rates of HT, while proximal HMCAS patients exhibited signi cantly lower ASPECTS compared to their proximal HMCAS-negative counterparts. This disparity in ASPECTS may account for the increased frequency of hemorrhagic transformation in patients with positive proximal HMCAS [14]. Previous studies have consistently demonstrated that HMCAS is correlated with larger cerebral infarct volumes, measured using the "one-third middle cerebral artery area" principle or ASPECTS on initial NCCT scans [5,[15][16][17], which is a well-established risk factor for HT following MT [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of proximal HMCAS was strongly associated with higher rates of HT, while proximal HMCAS patients exhibited signi cantly lower ASPECTS compared to their proximal HMCAS-negative counterparts. This disparity in ASPECTS may account for the increased frequency of hemorrhagic transformation in patients with positive proximal HMCAS [14]. Previous studies have consistently demonstrated that HMCAS is correlated with larger cerebral infarct volumes, measured using the "one-third middle cerebral artery area" principle or ASPECTS on initial NCCT scans [5,[15][16][17], which is a well-established risk factor for HT following MT [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent research has unveiled a link between asymptomatic hemorrhagic transformation (aHT) post-MT and worse functional results [21,22]. KANG et al [14] similarly identi ed that patients developing HT following MT reperfusion therapy, including aHT and sHT forms, exhibited lower rates of favorable outcomes. Correspondingly, in our study, HT was unequivocally linked to an unfavorable prognosis in CE patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Previous studies have consistently demonstrated that sICH is associated with an elevated risk of unfavorable clinical outcomes and a diminished benefit-to-risk ratio of EVT accordingly. [6][7][8] Hence, timely and precise identification of sICH following EVT holds importance for enhancing perioperative management and clinical prognosis.…”
Section: Introductionmentioning
confidence: 99%